Implementation of the Witness and Victim Protection Agency in Providing Protection to Victims of Vigilantes (Eigenrichting) - Fadilah, Nurul (Universitas Sultan Ageng Tirtayasa, 2023)
In Indonesia, witness and victim protection institutions (LPSK) need to be discussed in term of the implementation and its protection to vigilante’s victim. The normative law and secondary data are used to conduct this research. It can be seen that LPSK does not give the protection right yet to vigilante’s victim. It is caused by the victim does not apply for the protection right through the form as a mandatory. This situation leads ineffectiveness of the protection right to the vigilante’s victim from LPSK since some of the victim not ready to report or take an action after the crime occurred. Indeed, medical and psychological rehabilitation need to be fulfilled for the recovery because the victim mostly suffered physically and mentally due to the persecution. Even though the main victim passed away, but the family still have the right like restitution from the offender since qualified as secondary victim.